GD 424 – a helium-atmosphere white dwarf with a large amount of trace hydrogen in the process of digesting a rocky planetesimal. Issue 3 (26th December 2020) - Izquierdo, Paula; Toloza, Odette; Gänsicke, Boris T; Rodríguez-Gil, Pablo; Farihi, Jay; Koester, Detlev; Guo, Jincheng; Redfield, Seth
ABSTRACT: The photospheric metal pollution of white dwarfs is now well established as the signature of the accretion of planetary debris. However, the origin of the trace hydrogen detected in many white dwarfs with helium atmospheres is still debated. Here, we report the analysis of GD 424: a metal-polluted, helium-atmosphere white dwarf with a large amount of trace hydrogen. We determined the atmospheric parameters using a hybrid analysis that combines the sensitivity of spectroscopy to the atmospheric composition, log(H/He), with that of photometry and astrometry to the effective temperature, T eff, and surface gravity, log g . The resulting white dwarf mass, radius, and cooling age are $\mbox{$M_{WD}$}=0.77± 0.01\, \mbox{$M_{\odot }$}$, $\mbox{$R_{WD}$}=0.0109± 0.0001\, \mbox{$R_{\odot }$}$, and τcool = 215 ± 10 Myr, respectively. We identified and measured the abundances of 11 photospheric metals and argue that the accretion event is most likely either in the increasing or in steady state, and that the disrupted planetesimal resembles either CI chondrites or the bulk Earth in terms of its composition. We suggest that the observed 1.33 × 10 22 g of trace hydrogen in GD 424 was at least partly acquired through accretion of water-rich planetary debris in an earlier accretion episode.